2003
DOI: 10.1002/app.13312
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical, surface, and thermal properties of polyamideimide–polydimethylsiloxane nanocomposites fabricated by sol–gel process

Abstract: ABSTRACT:Polyamideimide (PAI)-epoxysilane (coupling agent) composites were reacted with oligomeric polydimethylsiloxane (PDMS), a condensation product of difunctional silane, by using the sol-gel process, and were then dried into films. After this procedure, the surface, mechanical, and thermal properties were measured. The study showed that PDMS existed in the PAI matrix by the use of FTIR. With respect to mechanical properties, the maximum elongation and toughness were increased in the PAI with silane groups… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
1

Year Published

2006
2006
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 33 publications
1
10
1
Order By: Relevance
“…Average porosity value was determined as 18% for the samples. This value is lower than reported for commercially used Celgard 2400 cell (41%) [45], but electrochemical results showed that even with this low porosity ionic conductivity values are more than sufficient. Lower porosity of 10PDMSFilm 2 may be caused by increase of the fiber diameter.…”
Section: Porosity and Electrolyte Uptake Of Membranescontrasting
confidence: 67%
See 2 more Smart Citations
“…Average porosity value was determined as 18% for the samples. This value is lower than reported for commercially used Celgard 2400 cell (41%) [45], but electrochemical results showed that even with this low porosity ionic conductivity values are more than sufficient. Lower porosity of 10PDMSFilm 2 may be caused by increase of the fiber diameter.…”
Section: Porosity and Electrolyte Uptake Of Membranescontrasting
confidence: 67%
“…This variety is the cause of synthesis and modification techniques. In our work, the glass transition temperature value of neat BTDA/ODA‐based fibrous PI was determined as 212°C and it is quite higher compared to Celgard cells which commercially used . The T g value of samples greatly increased after photocurable resin was applied to fibrous PI due to crosslinked structure formation.…”
Section: Resultsmentioning
confidence: 72%
See 1 more Smart Citation
“…The sample code is abbreviated based on the weight composition of the polysiloxane in the hybrids at the feed. were also confirmed [29,30].…”
Section: Preparation Of Polybenzoxazine-poly(dimethylsiloxane-co-diphsupporting
confidence: 64%
“…A low glass‐transition temperature in melting gels indicates a higher concentration of linear polymeric chains. The T g of PDMS, which is formed only from the linear polysiloxane chains is ~−100°C …”
Section: Discussionmentioning
confidence: 99%